The Development of Physics E-Module CTL-Based for Reflection and Refraction of Light Topic - Aprianti, Rika; Nadiyyah, Khoirotun; Gusti, Valeria Yekti Kwasaning; Herliana, Fitria (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
This study aims to develop an e-module based on Contextual Teaching and Learning (CTL) as a physics learning media and to test its feasibility. The study employed a research and development method (R & D). This research produces a digital learning media for the Physic topic of reflection of light and refraction of light, which can assist students in studying independently by following the syntax of CTL. The e-module combines video, audio, and interactive quiz features. The development process was conducted through the ADDIE model where the researcher evaluate every step in the development process. The e-module was developed according to the syntax of CTL. Validation of the e-module was conducted during the development steps. The validation results by the material expert gained a score of 85.09%, while the media expert gained a score of 82.14%. The e-module was implemented in a small group of nine students and gained a score of 84.71%. These scores mean that the e-module was considered feasible and very good.